Islamic Legal Policy on the Use of Social Media (Critical Study of MUI Fatwa) (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Technological developments have made it easier to access information from various places. Social media has become an inseparable part of every aspect of modern life, so it is necessary to have legal policies and guidelines in believing through social media. This study aims to find out a critical review of MUI fatwa policies in unravelling laws and guidelines for the use of social media. The research method used is normative legal research with a conceptual approach. The results of the study show that MUI Fatwa Number 24 of 2017 is the right response to ethical challenges that arise due to the use of social media. This fatwa provides clear guidance for Muslims on how to use social media ethically and by Islamic teachings. However, as a fatwa, this regulation does not have binding legal force, coercion and does not have legal sanctions whose settlement is through litigation or still based on laws and regulations, only functions as a moral guideline depending on individual awareness. Without stricter enforcement or appropriate legal regulations, the impact could be limited.